Decoding Regional Diversity: Physical and Socio-Economic Development Typology of Sub-Districts in Bogor Regency - Rosandi, Vely Brian; Pravitasari, Andrea Emma; Cesarini, Rifa Amalia (The Indonesian Journal of Planning and Development, 2025)
Bogor Regency as part of the Jabodetabek Megacity, serves as a satellite area for Jakarta and exhibits significant potential for land cover change. This study aims to: (1) analyze land cover change dynamics; (2) assess regional development levels in 2019 and 2022; (3) classify regions based on physical, social, and economic characteristics; and (4) analyze regional typology using the Sub-District Development Index (SDI), Human Development Index (HDI), and land cover percentage. Data from 2019 and 2022, including land cover maps, administrative maps, village potential, and HDI, were analyzed using overlay techniques, scalogram analysis, Klassen typology, and k-means clustering. Results indicate significant reductions in rice fields and dry agricultural land, primarily converted to built-up areas, especially in Cibinong Sub-district, driven by increased demand for space and economic facilities. Most regions in Bogor Regency exhibit low to very low development levels based on the availability and accessibility of education, health, and economic facilities. Klassen typology reveals a disparity, with some sub-districts progressing while others lag behind. The regional typology identifies three categories: rural areas in the east and west, urban areas in the north, and suburban areas dispersed across sub-districts.